The Role of Bandung Polrestabes Satlantas Personnel in the Implementation of Andalalin in Order to Realize Kamseltibcar Then - Laga, Mohammad Fatiyo Nadwa (Police Studies Review, 2024)
This research is motivated by the existence of social problems in traffic in the form of traffic jams that result in not achieving "kamseltibcar lantas" in the city of Bandung. The increased of transportation caused by the increasing of population is not the only source of problems, but because there are developments that have impact on traffic, so it requires Traffic Impact Analysis (Andalalin) to prevent traffic jams. Polrestabes Bandung Traffic Police is an organization that has a role in this phenomenon, it is necessary to have a capable ability related to Andalalin. This research aims to determine the ability condition of personnel in Polrestabes Bandung Traffic Police in assessing the Andalalin. The problems are discussed using Competency Theory, SWOT Analysis Theory, Cooperative Theory, and several concepts of statutory regulations such as UU No. 22 of 2009, PP RI No. 32 of 2011, and Permenhub No. 75 of 2015. The research was conducted with a qualitative approach method with the type of research descriptive research. Data collection techniques by interviewing, observing, and studying documents. Data analysis techniques with data reduction, data display, and verification. Based on the results of the research showed that there is still a lack of ability possessed by Polrestabes Bandung Traffic Police personnel, as assessed by indicators of knowledge, skill, and attitude. The factors that influence the ability of personnel are analyzed through internal factors consisting of strengths and weaknesses, as well as external factors consisting of opportunities and threats. The implementation of Andalalin was discussed using Permenhub No. 75 of 2015 concept. The conclusion in this research shows that in general, personnels of Polrestabes Bandung Traffic Police don’t understand about Andalalin. So the authors provide advices on the need for socialization related to Andalalin and increase the role of Pusdik Lantas specifically.